DYNAMICS OF PARASITE POPULATION, AND ITS HISTOPATHOLOGICAL AND HISTOPHYSIOLOGICAL EFECTS IN THE STOMACH OF A FRESHWATER FISH - Benarjee, G.; Reddy, Laxma; Krishna Prasad, K. S.; Srikanth, K.; Swamy, M.; Ramu, G.; Ramulu, K. Narasimha (Journal of Indian Fisheries Association, 2007)
The caryophyllaeid cestode Lytocestoides fossilis infects the freshwater catfish Heteropneustes fossilis. The study was conducted for two consecutive years (2004-06) to record the biostatistical data of the parasite. The incidence of infection, intensity of infection, density of infection and index of infection of the parasite has been recorded. The infection was more during June to September, moderate during February to May and low during October to January. The parasite brought about severe histopathological changes in the stomach of infected fish. The changes observed in the stomach of fish included structural damage of the villi, inflammation, and fibrosis associated with hyperplasia and metaplasia. The hypertrophy of mucous layer led to vacuolation and necrosis. Histochemical changes were noticed with enhanced carbohydrate, protein and lipid contents. The enhanced substrate content in the infected organ might be due to the disfunctioning of the digestive tract, which results in the accumulation of various metabolites. Mucus secretion was triggered as a protective interaction against parasitic invasion. The parasitic infection affects the general metabolic state of the host and as the result, the fish becomes sluggish and moribund. Keywords: Heteropneustes fossilis, Lytocestoides fossilis, histopathology, histochemistry